2017
DOI: 10.1111/lam.12709
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of Livestock-Associated MRSA in raw meat on retail sale in North West England

Abstract: Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is a public health concern worldwide, but has only been reported sporadically in the UK. In the largest UK study to date, samples of raw meat at retail sale were examined for both the presence and levels of MRSA. We report the first isolations of CC398 LA-MRSA from poultry meat in the UK including representatives of a particular sub-clade associated with cases of human infection/colonization in Europe. Although levels were low (<20 CFU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…Based on CLSI subclasses criteria, 27 out of 29 MRSA strains (93.1%) were multidrug-resistant MRSA strains ( Table 5 ). In several studies ( Abdalrahman et al., 2015 ; Fox et al, 2017 ; Li et al, 2017 ; Normanno et al, 2015 ), a large proportion of MRSA strains isolated from meat were also revealed to be multidrug-resistant. Ge et al (2017) reported that multidrug-resistance (MDR) rates in MRSA (37.2%, 29/78) were higher than those of methicillin-susceptible Staphylococcus aureus (MSSA) (8.2%, 78/954).…”
Section: Resultsmentioning
confidence: 99%
“…Based on CLSI subclasses criteria, 27 out of 29 MRSA strains (93.1%) were multidrug-resistant MRSA strains ( Table 5 ). In several studies ( Abdalrahman et al., 2015 ; Fox et al, 2017 ; Li et al, 2017 ; Normanno et al, 2015 ), a large proportion of MRSA strains isolated from meat were also revealed to be multidrug-resistant. Ge et al (2017) reported that multidrug-resistance (MDR) rates in MRSA (37.2%, 29/78) were higher than those of methicillin-susceptible Staphylococcus aureus (MSSA) (8.2%, 78/954).…”
Section: Resultsmentioning
confidence: 99%
“…In a single-hospital study in Germany, admission screening at one hospital identified 25% of MRSA isolates to be of livestock-associated type, yet LA-MRSA amounted to only 7% of MRSA isolates from clinical sample submissions (Köck et al, 2011). The identification since 2005 of widespread LA-MRSA colonization of pig herds in many countries with intensive pig production (EFSA, 2009;Lassok & Tenhagen, 2013), plus in retail pork and other meats (Fox et al, 2017;Lassok & Tenhagen, 2013;Verhegghe et al, 2016), has led to a focus on characterization and control of this AMR organism, plus substantial interest in the media and among a general public familiar with MRSA from healthcare and community sources.…”
Section: Current Issues For Amr In Livestock Bacteriamentioning
confidence: 99%
“…Despite the recognition of CC398 LA‐MRSA in neighbouring mainland Europe its epidemiology has been less well‐studied in the United Kingdom. Nonetheless, small numbers of CC398 MRSA isolates have been found, largely since 2012, from bovine milk (Paterson et al ), pigs (Hartley et al ; Hall et al ), poultry (Anonymous ), retail pork and poultry meat (Hadjirin et al ; Fox et al ), horses (Loeffler et al ; Bortolami et al ) and humans (Ward et al ; Harrison et al ; Kinross et al ) in the UK. Yet while clearly present in the UK and spread among different host species few data are available on the prevalence of CC398 MRSA in the UK human population.…”
Section: Introductionmentioning
confidence: 99%